Rapid, Sensitive and Validated Ultra-Performance Liquid Chromatography/Mass Spectrometric Method for the Determination of Fenofibric Acid and its Application to Human Pharmacokinetic Study. Issue 1 (2010) - Dubey, Sunil K.; Tomar, Manoj S.; Patni, Anil Kumar; Khuroo, Arshad; Reyar, Simrit; Monif, Tausif
Abstract : The first, rapid and sensitive ultra performance liquid chromatography mass spectrometric method for the determination of fenofibric acid, the active metabolite of fenofibrate, a lipid regulating agent, in human EDTA plasma has been developed and validated using fenofibric d6 acid as internal standard and Waters LC-MS/MS. Negative ions of fenofibric acid and fenofibric d6 acid were detected in multiple reaction-monitoring (MRM) mode. The method was validated over a concentration range of 0.176 μg/mL to 19.837 μg/mL (r ≥ 0.99). It took only 1.5 minute to analyse a sample. Intra- and inter-run precision of fenofibric acid assay at four concentrations ranged from 0.5% to 4.3% with accuracy varied from 93.1 to 108.1% indicating good precision and accuracy. Analytical recoveries of fenofibric acid and internal standard in plasma were less than 90%. This method was successfully applied for evaluation of pharmacokinetics of fenofibric acid after a single oral dose of 145 mg fenofibrate to 10 Indian healthy volunteers